MSS-1 ～ MSS-2 (The Japanese Journal of SURGICAL METABOLISM and NUTRITION, 2017)
INTRODUCTION: Prolonged physical exertion in hot and/or humid environments can induce physiological strain and increase the risk of heat exhaustion or exertional heat stroke (EHS). Heat acclimatization (HA) optimizes an individual's ability to tolerate heat and is therefore widely adopted to improve exercise performance in thermally challenging environments. Sweat is a key thermoregulatory indicator reflective of physiological adaptations during HA and hence is regarded as a valuable resource for monitoring HA. However, knowledge of molecular-level changes and adaptations in sweat associated with HA remain limited. METHODS: We exploited a non-invasive proteomics-based approach for identifying HA-associated protein changes in sweat. Advanced mass spectrometry-based proteome profiling was performed on sweat samples obtained from forehead and chest, collected before and after two weeks of isothermic conditioning (pre-IC/post-IC). The IC program was designed to elevate and maintain core temperature (Tc) ≥ 38.5 ℃ through jogging and circuit activities, thereby enhancing the thermal stimulus to confer a favourable heat-adapted phenotype. RESULTS: The sweat landscape revealed that HA profoundly modulated sweat protein compositions, with more pronounced effects post-thermal conditioning in forehead sweat compared to chest sweat. Functional correlation analysis of altered proteins indicated that heat adaptations involved close-knit crosstalk between proteins mediating heat response and immune-related proteins. We identified distinct-site specific alterations responsive to heat adaptation and observed that several of the top differentially expressed proteins post-IC were linked to immune processes such as B cell activation and interleukin signaling, and vasoregulation. Notably, proteins including IL1RA, UTS2, CALM1, and HPX showed consistent changes with thermoregulation across both sites, suggesting their potential to be explored as sweat-based biomarkers for monitoring individual responses to HA. CONCLUSIONS: Our findings demonstrate HA modulates sweat protein profiles in a site-specific manner and opens new avenues for exploring the utility of sweat-based protein markers for monitoring and evaluating heat acclimatization.